Our experience with choledochoscopy - Torterolo, Edgardo; Czarnevicz, Daniel; Ferreira, Carlos; Neirotti, Rubens; Secondo, Gerardo; Bergara, M; Carrerou, Luis A; Cidade, Luis; Beltrán, Ricardo (Cirugía del Uruguay, 1996)
The authors make a retrospective analysis of 198 cases of biliar lithiasis surgery 11 O cases had not undergone choledoscopy (group 1) and 88 cases had (group 2). They detail the most important technical steps, global and specific morbimortality The latter is higher far group 1. A remarkable decrease of residual lithiasis is pointed out far group 2. Conclusions: choledoscopy is an effective metho far decreasing complications in the biliar tree. Choledoscopy is not a substitute far cholangiography and its good results need a learning.